Analisis Retribusi Daerah Kota Samarinda - Annisa Darmawan; Fitriadi Fitriadi; Akhmad Noor (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
The purpose of this study was to is contributions and levies growth Samarinda according Typology Klassen. This study uses time series data in 2011-2015 and analysis tools Typology Klassen. Based on these results indicate that the regional Contributions levies on revenue in the city samarinda good enough, this was due to the contribution levies throughout the year is above average by size typology ability klassen.Pertumbuhan levies in Samarinda City area have increased and decreased , Each year the levy increase and decrease caused by local regulations. viewed from the position of comparative typology Klassen was above average based capabilities Klassen typology.Keywords: Contributions Levies Levies growth